Estimated dose exposure of the neonate to buprenorphine and its metabolite norbuprenorphine via breastmilk during maternal buprenorphine substitution treatment - Ilett, K.; Hackett, L.; Gower, Shelley; Doherty, D.; Hamilton, D.; Bartu, Anne (Mary Ann Liebert, Inc. Publishers, 2012)
Objective: The aim of the present study was to estimate the dose of buprenorphine and its primary metabolite norbuprenorphine that a breastfed infant would receive during maternal maintenance treatment with buprenorphine. Study Design: Seven pregnant opioid-dependent women taking buprenorphine (median, 7mg/day; range, 2.4–24 mg) and who intended to breastfeed were recruited. After lactation was established, several milk samples were collected from each subject over a 24-hour dose interval, and buprenorphine and norbuprenorphine concentrations were measured by liquid chromatography–tandem mass spectrometry. The average concentration (Cavg) across the dose interval was estimated as for both buprenorphine and norbuprenorphine (as buprenorphine equivalents). Absolute infant dose (AID), defined as Cavg daily milk intake, and relative infant dose (RID), defined as 100 AID/weight-adjusted maternal daily dose, via milk were calculated, assuming a milk intake of 0.15 L/kg/day. The infant’s health and progress were assessed directly and by questionnaire on the study day. Results: Mean (95% confidence interval) norbuprenorphine concentration in milk and AID values (1.94 [0.79–3.08] μg/L and 0.29 [0.12–0.46] μg/kg/day, respectively) were approximately half those for buprenorphine (3.65[1.61–5.7] μg/L and 0.55 [0.24–0.85] μg/kg/day, respectively). Similarly, the mean RID values were 0.18% (0.11–0.25%) for norbuprenorphine and 0.38% (0.23–0.53%) for buprenorphine. The breastfed infants showed no adverse effects, were all in good health, and were progressing as expected. Conclusion: Thus the dose of buprenorphine and norbuprenorphine received via milk is unlikely to cause any acute adverse effects in the breastfed infant.